Growth in East Asia : What We Can and What We Cannot infer. (Economic Issues; Economic Issues ;, 1996)
The spectacular growth of many economies in East Asia over the past 30years has impressed the economics profession, which often refers to thesuccess of the so-called Four Tigers of the region (Hong Kong, Korea, Singapore, and Taiwan Province of China) as "miraculous." This papercritically reviews the reasons alleged for this extraordinary growth.It weighs arguments in the debate over factor accumulation versustechnical progress, the role of public policy, the contribution ofinvestments and exports, and the influence of initial conditions onsubsequent growth.